(untitled) (Research, Society and Development, 2022)
The objective of this study was to verify the influence of allelopathic compounds released by Brachiaria brizantha cv. Marandu on the tolerance of plant growth-promoting bacteria (PGPB). Extracts of shoots and roots of B. brizantha were obtained at concentrations of 12.5; 25.0; 50.0 and 75.0% and evaluated the effect on the growth of 10 PGPB strains using agar drilling and serial dilution methodologies. The experiment was installed in a completely randomized design (CRD) in a factorial scheme, 10 x 5 x 2 with 4 replications, 10 bacterial strains, 5 constituting the four different concentrations and a control treatment (without extract) and 2 extracts of allelopathic compounds, shoot and root, of B. brizantha. Inhibition was verified by the root extract at a concentration of 75% for the UNIFENAS 100-01 strains; 100-13; 100-39; 100-02 and 100-94 by the agar perforation method. The other strains grew normally in the culture medium at all concentrations. According to the data obtained, it was possible to observe that allelopathic extracts of B. brizantha may interfere with the growth of PGPB strains, which may compromise their efficiency when used as inoculants.